2023
DOI: 10.1002/adhm.202300120
|View full text |Cite
|
Sign up to set email alerts
|

Surface Engineering of Central Venous Catheters via Combination of Antibacterial Endothelium‐Mimicking Function and Fibrinolytic Activity for Combating Blood Stream Infection and Thrombosis

Abstract: Long‐term blood‐contacting devices (e.g., central venous catheters, CVCs) still face the highest incidence of blood stream infection and thrombosis in clinical application. To effectively address these complications, this work reports a dual‐functional surface engineering strategy for CVCs by organic integration of endothelium‐mimicking and fibrinolytic functions. In this proposal, a lysine (Lys)/Cu2+‐incorporated zwitterionic polymer coating (defined as PDA/Lys/Cu‐SB) is designed and robustly fabricated onto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…36 Importantly, it was observed that the CMPU coating did not contribute to an additional foreign-body inflammatory response owing to its biocompatible zwitterionic interface. 11,41 This indicates that the CMPU coating not only possesses antibacterial properties but also exhibits favorable biocompatibility, making it a promising candidate for applications where minimizing bacterial infection and inflammatory response are crucial.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Importantly, it was observed that the CMPU coating did not contribute to an additional foreign-body inflammatory response owing to its biocompatible zwitterionic interface. 11,41 This indicates that the CMPU coating not only possesses antibacterial properties but also exhibits favorable biocompatibility, making it a promising candidate for applications where minimizing bacterial infection and inflammatory response are crucial.…”
Section: Resultsmentioning
confidence: 99%
“…5–9 Though systemic administration of antibiotics and anticoagulants has been a routine clinical protocol to mitigate infection and thrombosis, associated risks of post-operative bleeding, antibiotic resistance, and liver burden remain significant clinical concerns. 10–12 To replace the administration of antibiotics and anticoagulants, surface modification of blood-contacting devices with antifouling properties to effectively resist proteins, bacteria, and platelets has become a promising strategy to prevent infection and thrombosis. 13…”
Section: Introductionmentioning
confidence: 99%
“…Central venous catheters (CVCs), among other blood-contacting catheters, hold significant importance in the management of cardiovascular disease and cancer. Typically, materials such as silicone rubber (SR), thermoplastic polyurethane, and polyurethane are employed in the construction of CVCs. , These materials are preferred due to their exceptional biocompatibility, resistance to high temperatures, and corrosion resistance. , Nevertheless, protein, bacterial, and platelet adhesion in the bloodstream can lead to thrombosis and bacterial infections. ,, These issues mainly arise from the catheter’s inappropriate wettability and the lack of antimicrobial properties. , These challenges can significantly burden patients, potentially leading to treatment failure or even mortality. ,, A common clinical strategy for the treatment of infection and thrombosis is to give antibiotics and intravenous heparin (Hep) immediately before or after catheter implantation, which often faces problems such as the development of resistant organisms and thrombocytopenia due to excess Hep . Consequently, the development of antibacterial and anticoagulant catheters remains a formidable undertaking.…”
Section: Introductionmentioning
confidence: 99%
“…However, silver ion hydrophilic coating catheters cannot be adjusted according to infection conditions [ 14 ], and clinically, their antimicrobial effectiveness does not appear significant [ 15 ]. Antibiotic-eluting catheters have shown some improvement, but there are problems of antibiotic resistance and rapid depletion [ [16] , [17] , [18] ]. Some promising antimicrobial methods have not yet been widely used in the clinic, such as antimicrobial peptide (AMP) coated catheters.…”
Section: Introductionmentioning
confidence: 99%